IDENTIFICATION OF CAROTENOID COMPONENTS IN GREEN VEGETABLES AS BASIC INGREDIENTS FOR ALTERNATIVE FOOD SUPPLEMENTS - Mauizah Hasanah; Fatemah Rosma (Universitas Islam Negeri Ar-Raniry, 2024)
Carotenoid known as a precursor to vitamin A (β-carotene) is currently being developed as protection against cancer and heart disease, reducing eye disease, anti-oxidants, and regulators in the body's immune system. This study aimed to determine the carotenoid content in some green vegetables as an alternative to the basic ingredients of food supplements. This research was conducted in the biology education laboratory of Syiah Kuala University using direct observation methods that measure the absorbance value of carotenoids in 5 types of green vegetables, using a purposive sampling technique. The sample was first cut into small pieces and weighed 0.03 mg then extracted and the absorbance value was calculated using a spectrophotometer with a wavelength of 480, 663, and 664, measured by 5 treatments and 4 replications with a dilution of 20%, 40%, 60%, 80 %, and 100%. Samples that have been diluted are measured for the carotenoid content. The results showed that the highest content of carotenoid was found in long bean leaves and the lowest was in papaya leaves.